Impact of Postgrafting Immunosuppressive Regimens on Nonrelapse Mortality and Survival after Nonmyeloablative Allogeneic Hematopoietic Stem Cell Transplant Using the Fludarabine and Low-Dose Total-Body Irradiation 200-cGy - Koh, L.-P. (2011)
10.1016/j.bbmt.2007.03.002